2014
DOI: 10.3945/jn.113.183012
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Magnesium Intake Is Inversely Associated with Mortality in Adults at High Cardiovascular Disease Risk

Abstract: The relation between dietary magnesium intake and cardiovascular disease (CVD) or mortality was evaluated in several prospective studies, but few of them have assessed the risk of all-cause mortality, which has never been evaluated in Mediterranean adults at high cardiovascular risk. The aim of this study was to assess the association between magnesium intake and CVD and mortality risk in a Mediterranean population at high cardiovascular risk with high average magnesium intake. The present study included 7216 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 26 publications
0
37
0
2
Order By: Relevance
“…The lack of difference in magnesium intake in active and sedentary subjects and a similar percentage of subjects with a low magnesium intake suggest that both groups are at risk of magnesium deficiency and its consequences such as type 2 diabetes, CVD and cancer [15,17,23]. In addition, taking into account that 60% of body magnesium is stored in bones and magnesium plays an important role in vitamin D synthesis [36], it seems that in our participants inadequate magnesium intake together with low calcium and high phosphorus possibly contribute to decreased bone mineralization [5].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of difference in magnesium intake in active and sedentary subjects and a similar percentage of subjects with a low magnesium intake suggest that both groups are at risk of magnesium deficiency and its consequences such as type 2 diabetes, CVD and cancer [15,17,23]. In addition, taking into account that 60% of body magnesium is stored in bones and magnesium plays an important role in vitamin D synthesis [36], it seems that in our participants inadequate magnesium intake together with low calcium and high phosphorus possibly contribute to decreased bone mineralization [5].…”
Section: Discussionmentioning
confidence: 99%
“…KD have also been associated with an increase in size and volume of LDL cholesterol particles, which is considered to reduce cardiovascular risk by decreasing atherogenicity [81]. Nevertheless, several studies showed an increase in LDL cholesterol levels [82,83,85,86], but not significantly in the trial by Westman et al [85]; in these cases, KD were 139 …”
Section: Kd and Dyslipidemiamentioning
confidence: 99%
“…After excluding one study conducted in Spain [36], the association between increased dietary magnesium intake and CVD mortality was marginally significant (HR = 0.83, 95% CI: 0.69, 1.01; p = 0.06), which suggested a protective dose-response effect of dietary magnesium intake against CVD mortality. Excluding the study of Spain appears appropriate because the lowest intake was above the recommended dietary allowance.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…1) [11,12,14,21,[36][37][38][39][40]. These studies were published between 2005 and 2014 and comprised 449,748 individuals and 10,313 CVD deaths (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%